The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.optom.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the relative peripheral refraction effect of single vision and multifocal contact lenses measured using an autorefractor and an aberrometer: A pilot study

Abstract: For most test conditions, distinct differences were observed between the RPR measures obtained with the two modified instruments. The differences varied with CL design and centration. Although the pilot study supports the interchangeable use of the two instruments for on- and off-axis refraction in unaided eyes or eyes corrected with low/no spherical aberration; we advocate the use of the COAS-HD over the SN for special purposes like refracting through multifocal CLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…On the contrary, Omafilcon A MFCL N was the worst performing and most inferiorly decentered lens. Significant inferior contact lens decentration with Omafilcon A MFCLs has been reported previously 28 , 35 and may be due to a general looser fit with those lenses. It has been shown that a significant decentration can lead to an increase in odd higher-order aberrations, 28 which could have adversely affected the visual performance.…”
Section: Discussionmentioning
confidence: 71%
“…On the contrary, Omafilcon A MFCL N was the worst performing and most inferiorly decentered lens. Significant inferior contact lens decentration with Omafilcon A MFCLs has been reported previously 28 , 35 and may be due to a general looser fit with those lenses. It has been shown that a significant decentration can lead to an increase in odd higher-order aberrations, 28 which could have adversely affected the visual performance.…”
Section: Discussionmentioning
confidence: 71%
“…An alternative method of measuring refraction is with the Hartmann Shack aberrometer, for which measurements are taken through the entire pupil area and components of refraction are calculated based on the lower and higher order aberration values (even radial orders, preferably up to 6th order) which might provide a more accurate representation. Bakaraju et al 35 have found some considerable differences, when wearing contact lenses, between peripheral refractions with a Shin-Nippon NVision 5001 (Grand-Seiko, Toyko), which is similar to the Grand-Seiko WAM-5000, and a Hartmann-Shack instrument (COAS-HD, Wavefront Sciences, Albuquerque, USA). Lens type* F 2.3,40.9 = 7.7 p = 0.001 F 1.9,33.5 = 14.1 p < 0.001 F 2.3,41.7 = 10.0 p < 0.001 Test method F 1,18 = 0.2 p = 0.518 F 1,18 = 1.5 p = 0.24 F 1,18 = 2.5 p = 0.13 Visual field angle F 2.6,45.9 = 59.1 p = 0.010 F 2.8,50.3 = 41.2 p < 0.001 F 2.4,42.6 = 5.1 p = 0.007 Refraction group F 1,18 = 4.2 p = 0.056 F 1,18 = 0.5 p = 0.3 F 1,18 = 2.9 p = 0.105 Lens type 9 Test method F 2.2,40.1 = 1.6 p = 0.22 F 3,54 = 0.6 p = 0.62 F 3,54 = 3.8 p = 0.016 Test method 9 Visual field angle F 6.2,111.1 = 2.5 p = 0.025 F 5.2,93.8 = 0.7 p = 0.65 F 4.9,88.1 = 1.1 p = 0.36 Visual field angle 9 Refraction group F 3.9,69.7 = 2.7 p = 0.037 F 4.7,84.9 = 1.1 p = 0.37 F 4.4,79.8 = 1.2 p = 0.32 p Values < 0.004 are bolded.…”
Section: Discussionmentioning
confidence: 99%
“…Increased decentration of Proclear ® MFCL has been noticed earlier. 11 , 14 Lens parameters such as BC and CL Dia in combination with the related ocular parameters of the individual CCs and HVIDs can provide an indication of the differences found in lens centration. 21 Results from the current study showed that, independent of the group, the ratio of CC/BC and the ratio of HVID/CL Dia of the Proclear ® MFCLs were significantly smaller when compared to the control lens.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in ocular and lens design parameters, ie, base curve (BC) and diameter, and material properties can affect the fit of MFCLs and thereby lens centration. It has been reported 11 , 14 that some MFCLs (ie, Proclear ® MFCLs; CooperVision, Pleasanton, CA, USA) decentered more than others and that vision with those lenses was also more reduced. Based on these observations, it has been suggested that decentration of MFCLs might impact vision.…”
Section: Introductionmentioning
confidence: 99%